Trends in Topics and Discourse in 19th-Century Central American Poetry - Bonilla Navarro, José Francisco (2016)
The study is a historical exploration of certain aspects in the development of Central American poetry during the 19th century. It was carried out as part of a larger project for the recovery and analysis of documents corresponding to a significant manifestation in the genre of poetry which has been somewhat overlooked by literary critics. A description is provided of El Parnaso centroamericano (1882), with a commentary on selection criteria, the predominant issues, and the esthetic discourse tendencies of the poems collected: panegyric poetry, patriotic poetry, love poetry, and metapoetry.